Mengatasi psychological emptiness pada penderita skizofrenia dengan Art Therapy - Muhammad Azka Maulana (Universitas Muhammadiyah Malang, 2021)
People with schizophrenia have a high risk of attempting suicide. This research is a case study that aims to see the effectiveness of Art Therapy to reduce the intensity of suicide in schizophrenic sufferers. The method of data collection is using the Suicidality Intention Scale given before and before the intervention. After 10 intervention sessions, the results showed a decrease in the intensity of suicide. This result is relatively stable after therapy which is characterized by a decrease in the number of suicides.